METABOLIC SYNDROME: METHODS OF PREVENTION AND TREATMENT - GULCHEKHRA KHAMROEVNA RAZHABOVA; KAROMAT SHOYIMOVICH DZHUMAEV; KOMILOVA BAXMAL ODILOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
Metabolic syndrome (MS) is a complex of interrelated and modifiable risk factors for the development of cardiovascular diseases (CVD) and type 2 diabetes mellitus (diabetes) (as defined by the World Health Organization (WHO, 1999) and NCEP ATP III (2001) - National Cholesterol Education Program Adult Treatment Panel III - US National Cholesterol Reduction Program, III revision of therapy for adults) [1]. The main components of MS are disorders of carbohydrate metabolism, abdominal obesity, dyslipidemia, and arterial hypertension